A Validity of STEM-Based Physics Learning Video on Parabolic Motion for Senior High School Students - Yora Inda Lestari; Sardianto Markos Siahaan; Ismet Ismet; Nor Farahwahidah Abdul Rahman (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This article will focus on the validity criteria, with the aim of this research being to assess the extent to which the physics learning media specific to the parabolic motion subtheme in the form of videos developed can be considered valid. Methodology: This study used research and development (R&D) with the Alessi and Trollip model. The data collection technique was carried out through a validation sheet instrument conducted by 5 expert validators. The development of learning videos was carried out for class XI Senior High School 22 Palembang. Main Findings: The assessment of the content aspect of the material resulted in a CVI value of 0.93. Furthermore, the evaluation of the media presentation aspect attained a CVI score of 1, and the validation of the productivity and innovation aspects of the material also scored 1. Since the CVI scores are all at 1, it can be inferred that the instructional video created is both valid and appropriate for educational purposes. Novelty/Originality of this study: This research makes a real contribution in answering the needs of modern learning with the STEM approach and AI technology. The results of this media validation are expected to be a reference for further research and become an inspiration for educators in developing innovative learning media.